Development of Assessment Instruments for Learning Process of Mathematics in Drawing Geometry at the Elementary School Level of Karanganyar Regency - Anjaya, Perdana Dika; Susilaningsih, Endang; Yulianto, Agus (Universitas Negeri Semarang, 2019)
This research is motivated by the need for teachers to conduct assessment or assessment practices that are in line with the demands of the curriculum. The research aims to: (1) develop an assessment of the learning process in mathematics class V SDN; (2) improve the quality of assessment instruments for the mathematics learning process in the fifth grade of Karanganyar District Elementary School drawing space based on the 2013 curriculum. This type of research is R & D with the observation method. The results of the preliminary research in the form of observations of instruments that will be developed show that the instrument is in the medium category of 22 items and is in the bad category of 4 items. Subsequently given material enrichment which finally can improve the quality of the instrument into 19 medium categories and 7 good category questions. This R & D research uses instrument trials ranging from observation, instrument development to implementation. The sampling technique used purposive sampling, carried out in SD Negeri Karangnyar Regency class V with the subject of Drawing Geometry. Results of the research: at the initial stage (observation) there were 4 instruments in the bad category and 22 in the medium category. The revision is done by providing material reinforcement on items 17 and 19, which is about drawing perspective lines on pyramid and prisms. The development phase (test of improvement) experienced the medium category of 19 instruments and good categories into 7 instruments. The implementation phase of the instrument in the medium category 3 instruments is in the category of 23 instruments. So that it can be concluded that